2021
DOI: 10.1101/2021.11.23.21266487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intersecting single-cell transcriptomics and genome-wide association studies identifies crucial cell populations and candidate genes for atherosclerosis

Abstract: BackgroundGenome-wide association studies have discovered hundreds of common genetic variants for atherosclerotic disease and cardiovascular risk factors. The translation of susceptibility loci into biological mechanisms and targets for drug discovery remains challenging. Intersecting genetic and gene expression data has led to the identification of candidate genes. However, previously studied tissues are often non-diseased and heterogeneous in cell composition, hindering accurate candidate prioritization. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Importantly, the genetic variation in the Vcam1+ SMCs and Col2a1+ SMCs contributed to CAD heritability beyond other cell states, suggesting that these cell states are particularly important in understanding the pathobiology of atherosclerosis. This is also supported by other recent studies looking into the cell type specific expression of predicted GWAS target genes 45,46 . Substantial ongoing efforts are looking into applying CAD PRS in the clinical practice including risk prediction, patient stratification and treatment response.…”
Section: Discussionsupporting
confidence: 85%
“…Importantly, the genetic variation in the Vcam1+ SMCs and Col2a1+ SMCs contributed to CAD heritability beyond other cell states, suggesting that these cell states are particularly important in understanding the pathobiology of atherosclerosis. This is also supported by other recent studies looking into the cell type specific expression of predicted GWAS target genes 45,46 . Substantial ongoing efforts are looking into applying CAD PRS in the clinical practice including risk prediction, patient stratification and treatment response.…”
Section: Discussionsupporting
confidence: 85%
“…In order to determine the relevance of the obtained mouse experimental data to human diseases, we first determined whether modulated VSMC and osteochondrogenic populations exist in human atherosclerotic lesions. To this end, we obtained VSMCs and fibroblast-like cells from scRNA-seq data from a total of 48 patient samples across 4 previous studies (GSE155512, 14 n =3; GSE159677, 23 n =3; GSE131780, 29 n =4; Slenders et al, 35 n =38) and then integrated them with WT mice scRNA-seq data ( Figure S9A through S9H ). Joint clustering showed that, in accordance with previous reports, 14 16 both modulated VSMC (cluster 0) and osteochondrogenic populations (cluster 6) also exist in human atherosclerotic lesions ( Figure S9D ).…”
Section: Resultsmentioning
confidence: 99%
“…Our granular SMC annotations were also critical to define etiologic SMC phenotypes for cardiovascular diseases and traits. Previous work from our group and others [93][94][95] has established a substantial contribution of SMCs towards CAD risk. By leveraging larger cell numbers, we further separated the SMC signal to prioritize fibromyocytes and foam-like SMCs underlying cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 68%